2013
DOI: 10.1074/jbc.m112.426791
|View full text |Cite|
|
Sign up to set email alerts
|

Caspase 1 Activation Is Protective against Hepatocyte Cell Death by Up-regulating Beclin 1 Protein and Mitochondrial Autophagy in the Setting of Redox Stress

Abstract: Background:The role of caspase 1 in non-immune cells that do not express IL1␤/IL18, like hepatocytes, is largely unknown. Results: Caspase 1 activation limits excessive mitochondrial reactive oxygen species during oxidative stress by up-regulating beclin1 and mitochondrial clearance in hepatocytes. Conclusion: Caspase 1 is hepatoprotective after oxidative stress. Significance: Our findings suggest a novel role for caspase 1 activation in promoting adaptive responses to oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 43 publications
(47 reference statements)
10
74
0
Order By: Relevance
“…In the first model, AIM2 activation by host-derived dsDNA led to increased autophagic flux in hepatocytes after redox stress induced by hypoxia with reoxygenation (13). Moreover, in vivo induction of autophagy by AIM2 inflammasome was protective by inducing removal of ROS-generating mitochondria in the liver (13,53). Similar to the previous study with RalB, beclin1 was an important mediator in autophagy activation mediated by AIM2 (13,53).…”
Section: Selective Autophagy In Inflammasome Activationsupporting
confidence: 69%
“…In the first model, AIM2 activation by host-derived dsDNA led to increased autophagic flux in hepatocytes after redox stress induced by hypoxia with reoxygenation (13). Moreover, in vivo induction of autophagy by AIM2 inflammasome was protective by inducing removal of ROS-generating mitochondria in the liver (13,53). Similar to the previous study with RalB, beclin1 was an important mediator in autophagy activation mediated by AIM2 (13,53).…”
Section: Selective Autophagy In Inflammasome Activationsupporting
confidence: 69%
“…Additionally, a role of caspase-1 in facilitation of cytoprotective autophagy has been suggested during hypoxia-induced mitochondrial stress [67]. In hepatocytes of casp-1 -/ -mice levels of the common autophagy markers LC3 and Beclin-1 were found to be decreased compared to wild-type (WT) [67]. When Beclin-1 was overexpressed in these cells the group reported that impaired autophagic clearance of damaged mitochondria was restored to WT rates [67].…”
Section: Initiator Caspasesmentioning
confidence: 95%
“…Additionally, a role of caspase-1 in facilitation of cytoprotective autophagy has been suggested during hypoxia-induced mitochondrial stress [67]. In hepatocytes of casp-1 -/ -mice levels of the common autophagy markers LC3 and Beclin-1 were found to be decreased compared to wild-type (WT) [67].…”
Section: Initiator Caspasesmentioning
confidence: 99%
See 2 more Smart Citations